Ethics on the job cases and strategies - Pfeiffer, Raymond S. (Boston Wadsworth Cencage Learning, 2014)
ETHICS ON THE JOB guides the reader through a step-by-step analysis to help them make good decisions in the face of ethical conflict. With the RESOLVEDD strategy, the authors have devised a powerful system for ethical decision-making in the workplace, which they teach students to implement through timely case studies and detailed analyses. Students develop a working grasp of important philosophical principles and their application in ethical conflicts, and learn to apply the RESOLVEDD strategy to ethical issues in their own lives. A classic text in ethical decision-making, ETHICS ON THE JOB is widely used in business ethics classes and corporate training programs across the country.
Keywords: Business ethics